JAWAN RESPONSIBILITY PROVIDING PKWT COMPENSATION AT PT SOCFINDO PERKEBUNAN TANAH GAMBUS - Etty Uyun; Henry Aspan (Universitas Efarina, 2023)
The legal basis for the company's obligation to provide compensation to PKWT workers lies in government regulation number 35 of 2021, the Job Creation Law as an implementing regulation. The service period for PKWT employees who will be extended can be compensated according to existing regulations after the PKWT period of at least one year ends. This article aims to determine the implementation of PKWT compensation by companies to their employees as regulated in statutory regulations. The research method that the author uses is empirical which is carried out using data collection methods through interview techniques with sources and distributing questionnaires. This article has been prepared systematically in accordance with the results and discussion of the author's research. The results of this research are PT. Socfindo Perk.Tanah Gambus has tried to implement regulations regarding compensation but they have not been fully implemented.